Lúcio de Sousa. The Jewish Diaspora and the Perez Family case in China, Japan, the Philippines, and the Americas (16th Century). Macau, Fundaçao Macau/Centro Científico e Cultural de Macau, I.P., 2015, 268 págs., ISBN: 978-99937-1-164-3. - Pérez García, Manuel (Investigaciones de Historia Económica, 2019)
Sin resumen